2017
DOI: 10.1098/rspa.2017.0230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boundary conditions on bistable behaviour in axisymmetrical shallow shells

Abstract: Multistable shells are thin-walled structures that have more than one stable state of self-stress. We consider isotropic axisymmetrical shallow shells of arbitrary polynomial shapes using a Föppl-von Kármán analytical model. By employing a Rayleigh-Ritz approach, we identify stable shapes from local minima in the strain energy formulation, and we formally characterize the level of influence of the boundary conditions on the critical geometry for achieving bistable inversion-an effect not directly answered in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…In general, in-plane supports strongly favour bistable inversion, which confirms a recent observation in [34]. More interestingly, the influence of the stiffness ratio differs significantly, depending on the support conditions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In general, in-plane supports strongly favour bistable inversion, which confirms a recent observation in [34]. More interestingly, the influence of the stiffness ratio differs significantly, depending on the support conditions.…”
Section: Resultssupporting
confidence: 88%
“…To satisfy the boundary conditions of w ( a ) = 0, m r ( a ) = 0, substitute the following values in equation (3.3): A1=a1+βfalse(η1+aη2+a2η3+a3η4false)2emfalse0and2emA4=η1a(1+β)(β+ν)+η2a2(2+β)(1+β+ν)+η3a3(3+β)(2+β+ν)a4(4+β)(3+β+ν).}To account for the degenerate case of β = 1, we have to consider the term η 2 ρ 3 causing a non-vanishing shear-force at the centre. For this particular case, we substitute this term with the next one in the series in equation (3.3), η 2 ρ 6 , and achieve results barely distinguishable from those in our isotropic study [34].…”
mentioning
confidence: 99%
“…For a given set of geometric boundary conditions, the domes' energy landscape has been shown to depend only on the dome height, the sheet thickness, and the Poisson's ratio of the constituent material. [ 43,44 ] Domes may be patterned to further increase their potential to realize shape adaptation. [ 45 ] Previous work has also revealed that structures featuring a periodic array of domes can be fabricated from plastics or by stamping metal sheets at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study the displacement of a static shallow shell lying over a planar obstacle from the numerical point of view, using a suitable finite element method. Shallow shells theory, which is extensively described, for instance, in the books [ 16 ] and [ 44 ], is widely used in engineering (see, e.g., the papers [ 31 , 41 43 , 46 ]). According to this theory, the problem under examination is modelled in terms of a fourth-order differential operator (cf., e.g., [ 16 ]).…”
Section: Introductionmentioning
confidence: 99%